KAJIAN SEMANTIK ONOMATOPE BAHASA INDONESIA DALAM NOVEL PERFECT PARTNER KARYA LEA ARMILA - Safitri, Dwi Rahma; Prayogi, Rahmat (STKIP Pesisir Selatan, 2025)
This study aims to describe the forms and meanings of onomatopoeia found in the novel Perfect Partner by Lea Armelia and to explain their semantic functions within the context of the story. This research employs a qualitative descriptive method using the reading and note-taking technique to collect data in the form of onomatopoeic words that appear in the novel’s text. The data were analyzed using the referential equivalent method by considering the contextual meanings and the situations surrounding their use. The results reveal two types of onomatopoeia: those that imitate inanimate sounds and those that imitate sounds occurring in the surrounding environment. The identified sound forms include ting, tok-tok, tut, brak, bruk, tak, bug, and plak. Through the use of these onomatopoeic expressions, the author successfully creates realistic and expressive effects that make readers feel as if they can hear the events directly. Semantically, the onomatopoeia in this novel function as markers of contextual meaning that enrich the aesthetic and linguistic value of the literary work.